Estudos em Diabetes mellitus gestacional: da busca de um protocolo eficiente à investigação sobre o desenvolvimento neural da prole - Mascarenhas, Fernanda Naves Araújo do Prado (2023)
Introduction: Diabetes mellitus (DM) is a metabolic syndrome characterized by a dysfunction in the production, secretion and/or action of insulin, causing hyperglycemia. The changes in this disease are metabolic and structural, affecting various tissues. When the disease occurs during pregnancy, it is called gestational diabetes mellitus (GDM), and the hyperglycemic state affects the developing fetus and can cause various damages. Excess glucose can compromise neural cells that react through neurophysiological and structural changes, with impairments in the conduction of nerve impulses and changes in neurotransmitters, synaptic vesicles, and glial activity. Objectives: To develop and standardize an experimental model of induction of GDM that is efficient in Wistar rats, using streptozotocin (STZ), in addition to understanding whether offspring of diabetic rats present structural and/or functional impairment in the cerebellum. Methodology: The animals obtained were placed for mating and checking for the presence of sperm in the females' vaginal wash, indicative of the first pregnancy (G1), and after five days (G5) they were induced to diabetes while fasting, intraperitoneally, using STZ, 50 mg/kg. Weight and blood glucose levels were evaluated, pre-mating, on the seventh and seventeenth day of pregnancy, being considered diabetic when blood glucose levels ≥ 200 mg/dL, and markers of oxidative damage in plasma serum. After birth, the puppies underwent litter quality assessment (number of puppies, sex and stillbirths). Subsequently, the puppies underwent physical evaluation, body mass index and blood glucose (mg/dL), and were euthanized at the ages of seven, 30 and 90 days, with extraction and physical evaluation of the brains (g) and dissection of the cerebellum, these were prepared for histomorphometric, immunofluorescent analysis, and expression of target proteins, data indicative of inflammation, gliosis, oxidative imbalance and cell death. Furthermore, evaluate the functional impacts, the puppies were subjected to motor behavioral tests. Results: We achieved 55.6% success in obtaining the experimental model of GDM, because we were able to implement a sequence of essential care, with proof of the establishment of the pathology characterized by the evolution of weight gain, hyperglycemia, and oxidative damage in maternal blood, in addition to change in litter quality. The puppies of diabetic mothers had lower body mass indexes combined with low brain weight, cerebellar histomorphometry showed the presence of thinner cortical layers, with the presence of gliosis, in addition to an oxidative imbalance, and apoptosis. In addition to demonstrating less exploratory behavior. Conclusion: We obtained an efficient GDM induction protocol and the study of the offspring's cerebellum showed that hyperglycemia during the gestational period can interfere with the offspring's cerebellar development with a functional impact on the rats' adult life.